2015
DOI: 10.1177/1044207315576081
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Collaborative Leadership Among Parents of Children With Disabilities

Abstract: Parent involvement and leadership have evolved over time and carry different meanings within various educational contexts in the United States. In special education, parent involvement includes the roles that parents of children with disabilities play in the development of their children’s Individualized Education Programs (IEPs), as well as in leadership and policy development and evaluation. In spite of the purported benefits of parent leadership in educational planning and policy, little research has been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…While Grenweldge and Zhang (2012) found that structured training led to an increase in advocacy-related knowledge, the present study found that participation in advocacy activities also increased. The finding regarding increases in clarity of vision and in activities such as serving on community boards and committees and speaking out in public are closely aligned with Shepherd and Kervick’s (2016)finding that advocacy training increases personal growth and confidence and tends to expand in scope for many participants beyond an initial concern for one or more individuals to a broader focus on policy and systems issues.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…While Grenweldge and Zhang (2012) found that structured training led to an increase in advocacy-related knowledge, the present study found that participation in advocacy activities also increased. The finding regarding increases in clarity of vision and in activities such as serving on community boards and committees and speaking out in public are closely aligned with Shepherd and Kervick’s (2016)finding that advocacy training increases personal growth and confidence and tends to expand in scope for many participants beyond an initial concern for one or more individuals to a broader focus on policy and systems issues.…”
Section: Discussionmentioning
confidence: 62%
“…They found that program participants reported higher advocacy-related knowledge than a matched control group. Shepherd and Kervick (2016) evaluated the outcomes of the Parents as Collaborative Leaders project, which provided leadership training and individualized internship experiences to parents at the local, state, and national levels. Qualitative analysis of interview data from a subset of 12 participants found significant positive outcomes were reported including new skills, improved networking and collaboration, and an increase in leadership and policy activities.…”
Section: Leadership and Advocacy Training Effectivenessmentioning
confidence: 99%
“…Parents of children on the autism spectrum can provide insight on their child’s strengths and vulnerabilities, which can be utilised by teachers to tailor learning experiences (Volkmar et al., 2014). Extensive evidence exists for the effectiveness of active parental involvement in improving academic and social outcomes for students with disabilities (Shepherd & Kervick, 2016) and it is now commonly acknowledged that parental involvement is a crucial ‘best practice’ in the education of students with ASDs. However processes are seldom operationalised and sustained (Azad & Mandell, 2016).…”
Section: Family–school Partnershipsmentioning
confidence: 99%
“…Parents of a child with disability report that peers provide essential information that differs from that provided by professionals (Clifford and Minnes 2013). Encouragement by and collaboration with peers can help parents of children with disabilities to address their shared challenges (Shepherd and Kervick 2016).…”
Section: Introductionmentioning
confidence: 99%